PERKEMBANGAN DAN PERAN PERPUSTAKAAN KHUSUS BALAI ARKEOLOGI YOGYAKARTA SEBAGAI PENDUKUNG PENELITIAN ARKEOLOGI - Saputro, Bayu Indra (BALAI ARKEOLOGI PAPUA, 2012)
Library in the sense of the future is an organization run by some of the professional librarians who are experts in their fields. Libraries in the institutions of Yogyakarta Archaeological Center is a specialized library in charge of a store and display the information stored in it to users, particularly researchers in the work environment. Library also provides references to research literature users outside agencies, especially students majoring in Archeology, Antroplogi Science, History and all disciplines relating to research and development history and culture in Indonesia.